(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
This study analyzes authorship patterns by gender in the Boletín de la Sociedad Zoológica del Uruguay (BSZU), aiming to shed light on genderbased inequalities in zoological research publications in Uruguay. We reviewed publications from 2000 to 2023, focusing on authorship by gender and examining the roles of first and last authors, which are commonly associated with lead contributors and senior researchers, respectively. Our results reveal a significant underrepresentation of female authors in original articles and short notes, although a more balanced presence was observed in obituaries. Additionally, women were less likely to occupy first or last author roles, reinforcing the prevalence of the “glass ceiling” effect, which hinders women’s advancement in scientific careers. We also found that gender of last authors influenced the likelihood of first authors being female, highlighting collaborative dynamics. By categorizing works by taxonomic group, we identified specific areas where female participation is more prominent, which may aid future bibliometric analyses. The data obtained emphasize a longstanding gender disparity in zoological publications in Uruguay, underlining the need for measures that promote gender equity within scientific authorship.